Relationship between serum vascular cell adhesion molecule-1 and endothelin-1 levels with organ involvement and disease activity in systemic lupus erythematosus patients - Hajialilo, M; Tayari, P; Ghorbanihaghjo, A; Khabbazi, A; Malek Mahdavi, A; Rashtchizadeh, N (Lupus, 2018)
Background Endothelial dysfunction plays an important role in pathogenesis of systemic lupus erythematosus (SLE). Considering the importance of serum soluble vascular cell adhesion molecule-1 as the most abundant of the circulating adhesion molecules increased as a result of endothelial dysfunction and the role of endothelin-1 in pathophysiology of SLE, this study aimed to evaluate serum soluble vascular cell adhesion molecule-1 and endothelin-1 levels in SLE patients compared to healthy subjects. Methods In this cross-sectional study, 60 SLE patients according to the Systemic Lupus International Collaborating Clinics classification criteria for SLE and 40 age and sex-matched healthy controls were included. In patients, clinical examination was performed and SLE disease activity index was assessed. Serum endothelin-1 and soluble vascular cell adhesion molecule-1 levels were measured using ELISA kits. Results The mean ± standard deviation age of patients and controls was 31.91 ± 7.66 and 33.20 ± 10.08 years, respectively. Compared to healthy controls, serum soluble vascular cell adhesion molecule-1 (1023.8 ± 352.96 vs. 866.06 ± 109.91) and endothelin-1 (77.83 ± 16.27 vs. 54.45 ± 12.01) was significantly higher in SLE patients (P = 0.003 and P < 0.001, respectively). The most common organs involved in patients were skin, joint and kidney. There were no significant differences in serum soluble vascular cell adhesion molecule-1 and endothelin-1 levels according to organ involvement, activity of disease and the conventional serum markers of disease activity (P > 0.05). There was no significant correlation between disease activity, organ involvement and negative or positivity of autoantibodies as well as serum complement with endothelin-1 and vascular cell adhesion molecule-1 levels (P > 0.05). Conclusions Although our study revealed higher serum soluble vascular cell adhesion molecule-1 and endothelin-1 levels in SLE patients compared to healthy controls, there were no significant correlations between their serum levels with organ involvement and disease activity.